Estudo fitoquímico e atividades biológicas das folhas e galhos de Cordia insignis Cham. (Boraginaceae) - Correia, Francyne Carmem Santos (2016)
The Cordia insignis species, popularly known as "shorts-of-old", is distributed in the Northeast and Midwest in Cerrado environments. The tea leaves is used in the treatment of pain and rheumatism. This work describes for the first time the chemical and biological investigation of C. insignis species, in the search for isolation and characterization of its special metabolites. The steroids 3-O-β-D-glucopyranosyl sitosterol, 3-O-β-D- glucopyranosyl stigmasterol, β-sitosterol, stigmasterol and campesterol, the triterpenes α-amyrin and β-amyrin, the coumarin scoparone, the ureido allantoin and phenilpropanoid derived methyl caffeate were isolated from the branches. From the leaves were isolated two coumarins, the scoparone and scopoletin, allantoin, phenilpropanoid derived caffeic acid and methyl rosmarinate. The structure determination was performed using spectroscopic techniques 1H and 13C NMR (1D and 2D) and MS. The extracts and fractions were subjected to antimicrobial activity. No extract or fraction showed antibacterial activity. For fungal strains, hydroethanol crude extract and chloroform fraction obtained from the branches showed promising activity against C. albicans with MIC 500 and 125 μg/mL, respectively. The hydroethanol crude extract and hexane fractions, chloroform and ethyl obtained from the leaves, have proved active against strains of C. albicans, C. glabrata and C. krusei, with MICs ranging entre15,62 and 500 μg/mL. The hexane and ethyl acetate fraction also showed promising results against strains of C. neoformans, with MIC values of 125 and 250 μg/mL, respectively. In antileukemic activity, only hydroethanol crude extract of leaves showed satisfactory results across the line of promyelocytes cells HL-60. These xxi activities may be related to the presence of substances with antifungal and antileukemic activity.